Pengaruh Pemberian Kompres Daun Kubis Terhadap Pembengkakan Payudara Pada Ibu Postpartum - Pratiwi, Yopi Suryatim; Handayani, Sri; Ariendha, Dian Soekmawati Riezqy (Universitas Qamarul Huda Badaruddin, 2019)
The problem that can arise in the puerperium and lactation is breast swelling. The impact of breast swelling is a feeling of discomfort in the breast-shaped mother, hardened breasts, fever, the baby is difficult to suck the breasts, mastitis, and breast abscesses. Breast is needed. Some non-pharmacological treatments can be done, one of which is by giving a cabbage leaf compress. This study is a comparative literature that attempts to discuss the comparison of cabbage leaf compresses against breast swelling in postpartum mothers. The results of a review of 6 studies prove that cabbage leaf compresses are effective in reducing breast swelling. This is caused by cabbage leaves containing the amino acid methionine which functions as an antibiotic and other ingredients such as sinigrin (Allylisothiocyanate), mustard oil, magnesium, sulfur heteroside oxides which can help widen the body to absorb the fluid that is blocked in the breast can reduce breast swelling.